2007
DOI: 10.1002/j.2161-1912.2007.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Multicultural Training on Perceived Multicultural Counseling Competencies and Implicit Racial Prejudice

Abstract: this study examined the impact of multicultural training on multicultural counseling competencies and implicit racial prejudice. results of a multilevel modeling analysis showed that only the multicultural counseling course was related to a decrease in implicit racial prejudice and an increase in cultural self-awareness. implications for multicultural training are discussed.este estudio examinó el impacto de la formación multicultural en las competencias en consejería multicultural y el prejuicio racial implíc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 19 publications
6
100
0
1
Order By: Relevance
“…Different tests have been designed to assess participants' knowledge and learning of the facts and principles of diversity sensitivity presented during the training. For instance, the knowledge subscale of the MCI has been used in studies examining the impact of training on multicultural counseling competencies of school psychologists and clinical students (e.g., Castillo, 2007;Williams, 2005). This scale assesses a counselor's breadth and grasp of the knowledge base of multicultural counseling research, cultural information, and treatment strategies (Sodowsky, Taffe, Gutkin, & Wise, 1994).…”
Section: Diversity Training Outcomesmentioning
confidence: 99%
“…Different tests have been designed to assess participants' knowledge and learning of the facts and principles of diversity sensitivity presented during the training. For instance, the knowledge subscale of the MCI has been used in studies examining the impact of training on multicultural counseling competencies of school psychologists and clinical students (e.g., Castillo, 2007;Williams, 2005). This scale assesses a counselor's breadth and grasp of the knowledge base of multicultural counseling research, cultural information, and treatment strategies (Sodowsky, Taffe, Gutkin, & Wise, 1994).…”
Section: Diversity Training Outcomesmentioning
confidence: 99%
“…For those that do exist, the findings are promising in that they have shown that multicultural training can positively affect racial growth (Castillo, Brossart, Reyes, Conoley, & Phoummarath, 2007;Heppner & O'Brien, 1994;Neville, Lilly, Duran, Lee, & Browne, 2000;Parker et al, 1998;Rothman, Malott, & Paone, 2012). Scholars in those studies applied a similar mixture of pedagogical practices (e.g., didactic and experiential) to multicultural trainings that were largely general in nature (e.g., addressing various topics, such as gender, culture, and race).…”
mentioning
confidence: 84%
“…Correspondence concerning this article should be sent to Dorota Celinska at dcelinsk@roosevelt.edu and Roberto Swazo at roberto.swazo@uni.edu multicultural competencies regardless of the pedagogical approach (Brown, 2004;Castillo, Brossart, Reyes, Conoley, & Phoummarath, 2007;Cates, Schaefle, Smaby, Maddux, & LeBeauf, 2007; Chu-Lieu Chao, Wei, Good & Flores, 2011;Malott, 2010;Pack-Brown, Thomas, & Seymour, 2008;Sammons & Speight, 2008;Tomlinson-Clarke, 2000). However, it remains a paramount challenge to find the curriculum designs for implementing the multicultural standards that most effectively enables counselors in the field to apply their multicultural knowledge and skills with diverse populations.…”
Section: Author's Notesmentioning
confidence: 99%
“…One student was quoted as stating: "…I guess it's hard to teach multicultural students to be multicultural because it's something you grew up with and it's something that you automatically do" (Seward, 2013, p.70). Castillo et al (2007) and Kiselca, Maben, and Locke (1999) reported that students who participated in a multicultural training course gained insight into cultural biases and selfawareness of their own cultural identity. Similarly, students in CACREP-accredited programs who received multicultural training in the form of either a multicultural counseling course or program-wide infusion of multicultural content increased their multicultural knowledge (Cates et al, 2007).…”
Section: Multicultural Infusion Through the Program -Implicit Curricumentioning
confidence: 99%